2004
DOI: 10.1161/01.cir.0000129311.73402.ef
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Strain Imaging of Altered Myocardial Stiffness

Abstract: Background-In this study we evaluate the diastolic deformation of ischemic/reperfused myocardium and relate this deformation to tissue elastic properties. Methods and Results-Farm pigs were subjected to left anterior descending coronary artery occlusion followed by reperfusion to create either stunning (nϭ12) or transmural myocardial infarction (nϭ12). Ultrasound-derived radial strain rates (SR) and strain were measured in the ischemic and remote walls. Myocardial stiffness was estimated from diastolic pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
62
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 42 publications
9
62
1
1
Order By: Relevance
“…18,19 Postsystolic shortening or thickening is also a sensitive marker of ischemia and myocardial viability. 20,21 In our study, the akinetic but viable myocardium of patients with ABS showed more prominent postsystolic shortening.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Postsystolic shortening or thickening is also a sensitive marker of ischemia and myocardial viability. 20,21 In our study, the akinetic but viable myocardium of patients with ABS showed more prominent postsystolic shortening.…”
Section: Discussionmentioning
confidence: 99%
“…Voigt, et al 137 demonstrated that the quantification of postsystolic myocardial S estimated post‐systolic shortening in ischemic myocardium. Pislaru, et al 138 and Park, et al 139 showed that regional diastolic SR can evaluate diastolic stiffness during myocardial stunning and infarction, aiding in viability assessment. There is evidence in an animal model that segmental early diastolic SR correlates with the degree of interstitial fibrosis 139 .…”
Section: Diastolic Strain/strain Ratementioning
confidence: 99%
“…Conversely, strain is easier to quantify as it can be calculated through imagebased algorithms that track tissue motion. One method to measure strain is through a temporal integration of strain rate, which can be measured from the difference in tissue velocities at two points within the myocardium (Heimdal et al, 1998;Pislaru et al, 2004). Another method to measure strain is from the spatial gradient of tissue displacements.…”
Section: Introductionmentioning
confidence: 99%
“…These methods have shown promise in the detection of ischemic or infarcted myocardium (Garot et al, 1999;Lyseggen et al, 2005;Pislaru et al, 2004). However, without measuring stress, these images are vulnerable to misinterpretation as observed variations could be due to the intrinsic non-uniform deformation of the heart.…”
Section: Introductionmentioning
confidence: 99%